ASPEK SOSIOLOGIS PADA PROTAGONIS TOKOH FILM MENARUNG JIWANI - Made Rai Budaya Bumiarta (CALACCITRA: JURNAL FILM DAN TELEVISI, 2021)
A creativity can create a literary work by an author. Literary work can be interpreted as the result of human creation that contains elements of beauty in it. A film has its own artistic value, because a film is a combination of several types of art. The purpose of this study is to increase the love of the younger generation to the traditional cultural values of each region and to know the characteristics of the area. This research results in an assessment of the sociological aspects of the Menarung Jiwani film shop where this film tells of two friends who again find cooperation and togetherness in dancing the Barong dance.